Isolation of an escape-resistant SARS-CoV-2 neutralizing nanobody from a novel synthetic nanobody library - Dormeshkin, Dmitri; Shapira, Michail; Dubovik, Simon; Kavaleuski, Anton; Katsin, Mikalai; Migas, Alexandr; Meleshko, Alexander; Semyonov, Sergei (Frontiers in Immunology, 2022)
The COVID‑19 pandemic not only resulted in a global crisis, but also accelerated vaccine development and antibody discovery. Herein we report a synthetic humanized VHH library development pipeline for nanomolar-range affinity VHH binders to SARS-CoV-2 variants of concern (VoC) receptor binding domains (RBD) isolation. Trinucleotide-based randomization of CDRs by Kunkel mutagenesis with the subsequent rolling-cycle amplification resulted in more than 1e11 diverse phage display library in a manageable for a single person number of electroporation reactions. We identified a number of nanomolar-range affinity VHH binders to SARS-CoV-2 variants of concern (VoC) receptor binding domains (RBD) by screening a novel synthetic humanized antibody library. In order to explore the most robust and fast method for affinity improvement, we performed affinity maturation by CDR1 and CDR2 shuffling and avidity engineering by multivalent trimeric VHH fusion protein construction. As a result, H7-Fc and G12x3-Fc binders were developed with the affinities in nM and pM range respectively. Importantly, these affinities are weakly influenced by most of SARS-CoV-2 VoC mutations and they retain moderate binding to BA.4\5. The plaque reduction neutralization test (PRNT) resulted in IC50 = 100 ngand 9.6 ngfor H7-Fc and G12x3-Fc antibodies, respectively, for the emerging Omicron BA.1 variant. Therefore, these VHH could expand the present landscape of SARS-CoV-2 neutralization binders with the therapeutic potential for present and future SARS-CoV-2 variants.